PENGARUH INSENTIF PAJAK, KUALITAS PELAYANAN, DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Abdi Pradnyani, Ni Luh Putu Norma Dewi; Sasmitadewi, Putu Raih; Suprapto, Putu Adi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022, 2022)
Tax revenue has not been maximized and the tax ratio is still low because the level of compliance of MSME taxpayers has decreased. In the conditions of the Covid-19 pandemic, Direktorat Jenderal Pajak provides tax incentives to maintain compliance during the Covid-19 pandemic. The purpose of this study was to determine the effect of tax incentives, quality of service, and taxation understanding on MSME taxpayer compliance. The type of data used in this study is primary data obtained through a questionnaire. The sample in this study was based on the accidental sampling method with a sample of 100 MSME taxpayers registered at KPP Pratama Badung Selatan. The statistical test used to test the hypothesis is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 media. The results of this study indicate that tax incentives, quality of service, and taxation understanding have a positive and significant impact on MSME taxpayer compliance.